How can “small childcare” support “great happiness”? A study on inclusive childcare services for infants and toddlers aged 0–3 in Guangxi through the lens of the capability approach - Chen, Zhoupeng; Liu, Junzhu; Li, Chunhui; Kang, Qing; Tang, Yi (Frontiers in Public Health, 2025)
BackgroundUnder the “three-child” policy, the importance of childcare for infants and toddlers aged 0–3 has been emphasized. However, the implementation of universal childcare policies still faces problems such as supply–demand mismatches, uneven resource distribution, and insufficient supervision, which constrain families’ childcare capabilities.Research objectiveDrawing on Amartya Sen’s capability approach and taking Guangxi as the research area, this study analyses the dilemmas and challenges in the implementation of universal childcare policies, explores their impact on families’ economic, social, and informational capabilities, and proposes corresponding optimisation paths.Research methodsThe current implementation of universal childcare in Guangxi was systematically examined through a mixed-methods approach, combining questionnaire surveys with in-depth interviews.FindingsThe results show that the policy has improved families’ childcare capabilities to some extent. However, its effectiveness has not been fully realized due to irrational resource allocation, limited service capacity of childcare institutions, insufficient family capabilities, and imperfect mechanisms of collaborative governance.ConclusionBased on these findings, this paper proposes high-quality development paths including more precise financial subsidies, diversification of childcare supply, and strengthening of collaborative governance systems. These measures aim to enhance families’ childcare freedom and promote the goal of ensuring that every child has access to care.